2020
DOI: 10.1101/2020.04.22.20075564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical evaluation of an immunochromatographic IgM/IgG antibody assay and chest computed tomography for the diagnosis of COVID-19

Abstract: 2 3

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
3
33
0
1
Order By: Relevance
“…Another disadvantage of the RT-PCR test is that it takes some time before results are available (25)(26)(27)(28), with estimated testing times ranging from 50 minutes to 4 hours for semiautomated to fully automated, walk-away assays and 6-14 hours for manually performed assays (29). Finally, although rapid point-of-care immunodiagnostic tests are being developed and investigated, their use for patient care is currently not recommended (25)(26)(27)(28).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Another disadvantage of the RT-PCR test is that it takes some time before results are available (25)(26)(27)(28), with estimated testing times ranging from 50 minutes to 4 hours for semiautomated to fully automated, walk-away assays and 6-14 hours for manually performed assays (29). Finally, although rapid point-of-care immunodiagnostic tests are being developed and investigated, their use for patient care is currently not recommended (25)(26)(27)(28).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…In total, 4696 records based on screening of titles or abstracts and 235 after full text review were excluded. Forty studies totalling 73 study arms15161718192021222324252627282930313233343536373839404142434445464748495051525354 met the inclusion criteria. Table 1 summarises the studies by test method; the sum of the number of studies exceeds 40 because some evaluated more than one method.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the studies by test method; the sum of the number of studies exceeds 40 because some evaluated more than one method. Seventy per cent (28/40) of the studies were from China,16171819202122232425262728293031323334353839404145464748 8% (3/40) from Italy,153643 and the remainder from the United States (3/40),425052 Denmark (1/40),51 Spain (1/40),37 Sweden (1/40),53 Japan (1/40),44 the United Kingdom (1/40),49 and Germany (1/40) 5433…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been demonstrated that the timing of sampling re lects in the sensitivity and speci icity of serological tests. Imai, et al [15] show that the sensitivity of IC assay was low during the early phase in symptomatic and asymptomatic patients. Cassaniti, et al [16] reported that the VivaDiag ® COVID-19 IgM/IgG Rapid Test present a weak positive serology in acute patients.…”
Section: Resultsmentioning
confidence: 99%